The good life - Rakfeldt, Jaak (Psychiatric Services, 2006)
Keywords: dept.swk

Assertive outreach: An effective strategy for engaging homeless persons with substance use disorders into treatment - Fisk, Deborah; Rakfeldt, Jaak; McCormack, Erin (American Journal of Drug and Alcohol Abuse, 2006)
The purpose of this study was to examine substance abuse treatment referrals that were made by outreach workers in a homeless outreach project. Ten outreach workers completed questionnaires on each of their clients who they had referred to a substance abuse treatment program over the previous year. Additional data was collected on the client's motivation level at the point the referral was made, which agencies the client was referred to, and if the client was rejected from any of the treatment programs. Bivariate correlation analyses were used to examine relationships between the variables. Of 73 project clients who were referred to substance abuse treatment in a one-year period of time, 41% successfully entered treatment. As might be expected, there was a statistically significant relationship between clients' motivation level and completed referral, and between referrals made and program acceptance. This study provides evidence that assertive outreach is effective in engaging and linking homeless persons with substance use disorders to substance abuse treatment services.
Keywords: Adolescent; Adult; Assertive outreach; Community-Institutional Relations; Female; Homeless Persons; Homeless populations; Humans; Male; Middle Aged; Substance abuse; Substance-Related Disorders; Treatment Outcome; adult; article; assertiveness; correlation analysis; dept.swk; drug dependence treatment; female; homelessness; human; major clinical study; male; mental health service; motivation; patient referral; social work; social worker; statistical significance; substance abuse